2015
DOI: 10.1045/january2015-henderson
|View full text |Cite
|
Sign up to set email alerts
|

Data Citation Practices in the CRAWDAD Wireless Network Data Archive

Abstract: Abstract. CRAWDAD (Community Resource for Archiving Wireless Data At Dartmouth) is a popular research data archive for wireless network data, archiving over 100 datasets used by over 6,500 users. In this paper we examine citation behaviour amongst 1,281 papers that use CRAWDAD datasets. We find that (in general) paper authors tend to cite datasets in a manner that is sufficient for providing credit to dataset authors, but also providing access to the datasets that were used. Only 11.5% of papers did not do so;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…The percentage of data citation (11.6%) is much lower than other studies. Mooney's () study, which analysed data citations using bibliographies from ICPSR in social sciences, reported 29%, and the study by Henderson and Kotz (), which analysed scholarly articles used Community Resource for Archiving Wireless Data At Dartmouth (CRAWDAD), reported that 88.5% cited a dataset. However, it was observed that the percentages of HINTS data citation improved from 5.6% (2005–2008) to 15.2% (2013–2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The percentage of data citation (11.6%) is much lower than other studies. Mooney's () study, which analysed data citations using bibliographies from ICPSR in social sciences, reported 29%, and the study by Henderson and Kotz (), which analysed scholarly articles used Community Resource for Archiving Wireless Data At Dartmouth (CRAWDAD), reported that 88.5% cited a dataset. However, it was observed that the percentages of HINTS data citation improved from 5.6% (2005–2008) to 15.2% (2013–2016).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated that researchers use a wide variety of ways to refer to datasets (Callaghan, ; Henderson & Kotz, ; Major, ; Mooney, ; Pepe, Goodman, Muench, Crosas, & Erdmann, ; Zhao et al, ). Belter () supported this by noting that 377 variant formats of citing the same data were found.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, a fundamental requirement for citation methods is to automatically create citation snippets in order to ensure consistency of references (Thorisson, 2009). Indeed, recent studies about data citation practices showed that data citation snippets are often underspecified, with vital information missing (Mathiak & Boland, 2015), and may present several errors compromising the identification and retrieval of the data being cited (Henderson & Kotz, 2015). Automatic methods for building citation snippets are also required because humans cannot remember or know what the necessary information is, when a snippet is complete, what the citation format requires in a given context, and where to gather the relevant information, especially in a big data context where manual exploration of data is unfeasible (Buneman et al, 2014;Crosas et al, 2015;Jagadish, 2015;Minister, 2012;Peters, Kraker, Lex, Gumpenberger, & Gorraiz, 2016).…”
Section: What Data Citation: Principles and System Requirementsmentioning
confidence: 99%
“…This system needs to be extended/revised to handle the citations of big dynamic data in order to be able to cite a subset of data on 1) selected variables and observations for large quantitative data; 2) time-stamp intervals; and, 3) spatial dimensions and also to be able to handle queries to the data. The use of DOI raised some concerns about the cost of minting identifiers for large data archives (Henderson & Kotz, 2015). Buneman and Silvello (2010) and Silvello (2017) discussed the case of XML data, where every single node of an XML file can be a citable unit.…”
Section: Identificationmentioning
confidence: 99%